2020
DOI: 10.1093/intqhc/mzac025
|View full text |Cite
|
Sign up to set email alerts
|

The future of quality and accreditation surveys: Digital transformation and artificial intelligence

Abstract: Accreditation is documented and reported by the external evaluation organization that the health facility provides services at certain standards. While on-site survey practices are being carried out by external evaluation organizations, there has been a trend toward new survey approaches using digital technologies as a result of the research carried out to ensure efficiency in surveys as well as improved effectiveness. With the emergence of the Covid-19 epidemic, external evaluation organization in all sectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Around this goal, the field of AI has gradually developed and given birth to numerous sub technologies to enable human-machine "communication" and machine "understanding and response" to humans, which are functions that coincide with the task of the discipline of "emotional interaction. These functions coincide with the task of the discipline of "emotional interaction" [2][3][4][5]. In fact, AIrelated technologies will support the main trends of future human-machine "multimodal interaction, natural interaction, physical interaction, and emotional interaction" and reshape the disciplinary paradigm of interaction design [6][7].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Around this goal, the field of AI has gradually developed and given birth to numerous sub technologies to enable human-machine "communication" and machine "understanding and response" to humans, which are functions that coincide with the task of the discipline of "emotional interaction. These functions coincide with the task of the discipline of "emotional interaction" [2][3][4][5]. In fact, AIrelated technologies will support the main trends of future human-machine "multimodal interaction, natural interaction, physical interaction, and emotional interaction" and reshape the disciplinary paradigm of interaction design [6][7].…”
Section: Introductionmentioning
confidence: 90%
“…Order fulfillment cost refers to the cost incurred by the supplier to convert the orders of individual outlets into shipments sent to an outlet i in one phase through a unified distribution center. , 4 7 8…”
Section: E-commerce Operation Cost Modelmentioning
confidence: 99%
“…Tong et al analyzed the impact of digital economy development on industrial structure based on panel data of 30 provinces in China and found that digital economy can drive industrial structure to rationalize development [ 33 ]. From the perspective of the labor force, the improvement of digital technology and the construction of digital platforms will greatly increase the production cost of enterprises, but it would promote the improvement of staff quality and make the industrial structure tend to be rationalized [ 34 , 35 ]. Fossen and Sorgner conducted an in-depth study on the impact of digital transformation on production methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of digital transformation, enterprises must strengthen the network security and privacy protection of financial data [9]. In addition, effective data encryption, access control, and network security strategies need to be adopted to prevent data leakage and cyberattacks [10]. Digital transformation is not only a technological change but also involves the transformation of the organizational culture and the ability of the staff [11].…”
Section: Introductionmentioning
confidence: 99%